AutoML and KaizenML - Chapter 5 Walkthrough Practical MLOps - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
A walkthrough of Chapter 5 of the O'Reilly book Practical MLOps. Topics include: * Getting models into production * Feature Store vs Data Warehouse * AutoML * MLOps * DataOps * ML Platforms * Sagemaker * Continuous Integration and Continuous Deployment * MLOps cookbook * ML Engineering * Data Engineering * Spark * GCP * Azure * Containers * Kaizen.